2010
DOI: 10.1097/coc.0b013e3181bead63
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Bone or Cartilage Invasion of Locally Advanced Head and Neck Cancers

Abstract: This study suggests similar outcomes between patients with bone or cartilage invasion treated with upfront CRT or resection followed by CRT. Concurrent CRT may be viable alternative to resection in patients with either bone or cartilage invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…It was therefore recommended to treat advanced carcinomas primarily by surgery with or without adjuvant radiotherapy . Although newer reports studying the outcome of definitive radiotherapy of advanced NV‐SCC are missing, there are counterparts analyzing results of head and neck‐SCC attributing similar results to definitive chemoradiation and surgery with postoperative chemoradiation of tumors with extensive soft tissue, cartilage, or bone involvement . Our data support these findings with 3 of 4 patients whose T4 tumors could be controlled successfully by definitive radiation therapy.…”
Section: Discussionsupporting
confidence: 77%
“…It was therefore recommended to treat advanced carcinomas primarily by surgery with or without adjuvant radiotherapy . Although newer reports studying the outcome of definitive radiotherapy of advanced NV‐SCC are missing, there are counterparts analyzing results of head and neck‐SCC attributing similar results to definitive chemoradiation and surgery with postoperative chemoradiation of tumors with extensive soft tissue, cartilage, or bone involvement . Our data support these findings with 3 of 4 patients whose T4 tumors could be controlled successfully by definitive radiation therapy.…”
Section: Discussionsupporting
confidence: 77%
“…Post-surgical combined radiotherapy and chemotherapy are also helpful and are reported to increase the overall survival rate [78]. For example, Ly et al showed that similar outcomes would be achieved, between patients with bone or cartilage invasion treated with primary chemoradiotherapy (CRT) or resection followed by CRT [79]. However, the protocols of these postoperative therapies vary in different clinical centres and can only be applied in a subpopulation of OSCC patients.…”
Section: Discussionmentioning
confidence: 95%
“…Subset analysis of the CRT group found no differences in LC (50% and 56% at 5 years, respectively) or OS in 26 patients with bone and/or cartilage invasion compared to 42 patients with other T4 criteria. The same group later demonstrated no difference between bone or cartilage invasion [11]. Samant et al [12] also reported no difference in outcomes based on bone versus cartilage invasion in 45 patients treated with intra-arterial cisplatin and concurrent RT (CRT).…”
Section: Discussionmentioning
confidence: 99%